Systematics and Conservation of Neotropical Amphibians and Reptiles - Catenazzi, Alessandro; von May, Rudolf (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book includes all 14 articles contributed to the Special Issue "Systematics and Conservation of Neotropical Amphibians and Reptiles" in the journal Diversity, originally published in 2019 and 2020.